Knowledge and Practices of Nurses Concerning Nursing Management for Patients with Skin Traction at Orthopedic Wards in Al- Hussein Teaching Hospital in Al-Samawa City - Kadush, Amer J.; H. Attia, Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: • Assessing nurses’ knowledge concerning management of patients undergoing skin • Evaluation of nurses’ practices concerning management of patients undergoing skin • Determine nurses’ knowledge and practice in relation to their demographic characteristics (age, gender, marital status, level of education, total years of service, total years of experience in orthopedic wards, number of training sessions in Iraq, and number of training sessions outside of Iraq). Methodology: A descriptive design was conducted on Nurses’ Knowledge and Practices Concerning Nursing Management for Patients with Skin Traction at Orthopedic Wards in Al-Hussein Teaching Hospital in Al-Samawa City. This study started from 16st of September 2019 up to 16th March 2020. Samples of (25) nurses who work in the orthopedic wards, (13) male and (12) female from the both morning and evening shift who are working in the hospital during the time of the study period and met the study criteria and agreed to participate in the study. Results: the study result indicated that the majority of the study samples had moderate knowledge level classification in all domains of the study, and the majority of the study samples had poor practices level classification in all domains of the study. Conclusions: the study concludes that nurses had a moderate knowledge level and a poor performance practices toward skin traction in the orthopedic wards. Recommendations: The researcher recommends providing educational programs for nurses to emphasize the practical implementation and to increase knowledge level regarding management of skin traction patients.